The Pros and Cons of Various Methodological Approaches to Deixis Research - Žic Fuchs, Milena (Array, 2000)
Various methodological approaches to deixis were analyzed, such as recordings of spoken language, comic strips and interviews. The analysis of Croatian deicic paradigms shows that a combination of methods is the best approach.